"It's a tradition of naming injustice": An oral history of the social determinants of health – Canadian reflections, 1960s-present. (December 2018) - Lucyk, Kelsey
Abstract: The 'social determinants of health' (SDOH) approach in Canada is widely acknowledged as having emerged through contributions such as the 1974 Lalonde Report or 1986 Ottawa Charter. Drawing on original oral histories, I consider this history through the reflections of past and present leaders in Canadian public health. Through this rich information, I identified three phases in the recent history of the SDOH, from a social awareness (1960s-1970s, when participants underwent training and gained exposure to social and health inequities), to a loose collection of theoretical and empirical concepts (1970s–1990s, when the evidence base on health inequities and the mechanisms behind them began to solidify), to a distinct research approach (2000s-present, when high profile events led to acceptance of the SDOH approach) that encompassed the spirit of its previous iterations. This paper will be of interest to health researchers and professionals, decision-makers, and trainees as they contemplate their own role in this ongoing history. Highlights: Social justice has remained core to SDOH history since the 1960s. Canada has contributed to a rhetoric supportive of the SDOH that helped shape this history. A generation of public health leaders committed to reducing health inequities emerged from the Canadian setting. The SDOH will continue to evolve as trainees learn from and build on its history.